Environment-friendly pressure-resistant inner tube and preparation method thereof
By adding modified waste butyl rubber, EVA resin and filler with specific ratios to the master glue body, and using stearic acid as an activator, a stable crosslinking network is formed, and the use of waste butyl inner tubes in the prior art is solved. The problems and poor desulfurization treatment effect have achieved the improvement of the performance of the environmentally friendly pressure-resistant inner tube and the maximum utilization of resources.
Patent Information
- Application Number
- CN202411569871.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The prior art is difficult to effectively utilize waste butyl inner tubes, resulting in environmental pollution and waste of resources. At the same time, the waste butyl rubber after desulfurization is not effective in using fresh rubber.
By adding modified waste butyl rubber, EVA resin and specific ratio fillers to the master glue body, and using stearic acid as an activator, desulfurization and modification treatment is carried out to form a stable cross-linking network and improving the pull of the inner tube Extension strength and heat-resistant air aging properties.
The tensile strength, elongation of break, tear strength and thermal tensile deformation of the environmentally friendly pressure-resistant inner tube are improved, and the comprehensive performance of the inner tube is improved, and the problems of environmental pollution and resource waste are solved.
Smart Images

Figure CN119431965A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tires, and in particular relates to an environmentally friendly pressure-resistant inner tube and a preparation method thereof. Background Art
[0002] Inner tube, commonly known as inner tube, refers to a circular elastic tube with a tire valve used to maintain the internal pressure of the tire. The valve is used to inflate and keep the air at a certain pressure in the inner tube. Inner tubes are generally made of butyl rubber.
[0003] With the rapid development of butyl inner tubes, a large number of scrapped butyl inner tubes will be produced every year. Since they cannot be naturally decomposed, many waste inner tubes are treated as waste and garbage, which not only pollutes the environment, but also causes a large amount of resource waste. Recycling and reusing waste automobile inner tubes, processing and reproducing them, and realizing the recycling of waste inner tubes can solve the problem of environmental pollution and maximize the utilization of resources.
[0004] At present, the treatment of waste butyl inner tubes is mainly through desulfurization. However, the waste butyl rubber after desulfurization is still a highly saturated and relatively inert material. When this material is mixed with fresh rubber, the chemical bonding ability between it and the fresh rubber is not ideal, and the product cannot meet the needs of consumers.
[0005] Therefore, there is an urgent need for an environmentally friendly pressure-resistant inner tube and a preparation method thereof. Summary of the invention
[0006] The purpose of the invention is to provide an environmentally friendly pressure-resistant inner tube and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing an environmentally friendly pressure-resistant inner tube, the method comprising the following steps: by weight:
[0009] (1) Weighing the raw materials of the masterbatch, specifically including the following components in parts by weight: 60-65 parts of butyl rubber, 35-40 parts of modified waste butyl rubber, 6-11 parts of EVA resin, 5-10 parts of chloroprene rubber, 70-75 parts of carbon black, 4-9 parts of modified filler, 6-12 parts of paraffin oil, 3-6 parts of crosslinking agent, 1-1.5 parts of stearic acid and 1.6-1.8 parts of sulfur;
[0010] (2) Add butyl rubber, modified waste butyl rubber, chloroprene rubber and EVA resin into a closed rubber mixer and knead at 120-130° C. for 5-7 min; continue to add carbon black and modified filler under heat preservation conditions and knead for 2-3 min; finally, add the remaining components and knead at 110-120° C. for 5-7 min to obtain a rubber mixture, shape the rubber mixture to obtain a tire tube, and vulcanize the tire tube to obtain an environmentally friendly pressure-resistant inner tube.
[0011] Furthermore, the preparation method of the modified waste butyl rubber comprises the following steps:
[0012] (1) washing the waste butyl rubber, drying it, and crushing it using a crusher to obtain rubber particles of 60-100 mesh;
[0013] (2) 16-20 parts by weight of a softener, 1-3 parts of an activator and 100 parts by weight of rubber particles are mixed, stirred evenly, loaded into a desulfurization device, desulfurized at 200-220° C. for 10-15 min, cooled, and a desulfurized rubber material is obtained;
[0014] (3) 100 parts by weight of devulcanized rubber material, 10-13 parts by weight of hydroxyl-containing unsaturated ester and 1-3 parts by weight of benzoyl peroxide are mixed, stirred at 120-130° C. for 2-3 hours, and cooled to room temperature to obtain modified waste butyl rubber.
[0015] Furthermore, the softener is a mixture of rapeseed oil, cottonseed oil and rubber seed oil in a weight ratio of 1:(1.2-1.4):(0.5-0.8).
[0016] Furthermore, the activator is stearic acid.
[0017] Further, the hydroxyl-containing unsaturated ester includes pentaerythritol diacrylate monostearate, polydipentaerythritol pentaacrylate and pentaerythritol triacrylate in a weight ratio of 1:(1.2-1.4):(0.5-0.7).
[0018] Pentaerythritol diacrylate monostearate, CAS: 92092-01-8, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.
[0019] Polydipentaerythritol pentaacrylate, CAS: 60506-81-2. Hubei Qiniu Chemical Technology Co., Ltd.
[0020] Pentaerythritol triacrylate, CAS: 3524-68-3.
[0021] Furthermore, the cross-linking agent is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, and methylene diphenyl diisocyanate.
[0022] In the prior art, the desulfurization process of waste butyl rubber is to increase the plasticization degree of the waste rubber by destroying its cross-linking network, so as to facilitate better fusion with fresh rubber and other materials. However, the use effect of the waste butyl rubber after desulfurization treatment is not ideal. The present invention uses stearic acid as an activator to make the desulfurization more thorough, and uses a hydroxyl-containing unsaturated ester to modify the desulfurized rubber material, and mixes it with the remaining components to improve the tensile strength of the environmentally friendly pressure-resistant inner tube. The analysis shows that after the hydroxyl active group is introduced into the desulfurized rubber material by grafting, a cross-linking network can be formed with the cross-linking agent in the system, and the complex molecular chain of the hydroxyl-containing unsaturated ester can further increase the complexity of the cross-linking network, and improve the tensile strength of the environmentally friendly pressure-resistant inner tube through synergistic effect. However, the elongation at break under this condition is not ideal.
[0023] Furthermore, the vulcanization conditions are: vulcanization temperature 170-180° C., vulcanization time 5-8 minutes, and pressure 0.6-0.9 MPa.
[0024] Furthermore, the EVA resin comprises EVA resin No. 1, EVA resin No. 2 and EVA resin No. 3 in a weight ratio of 1: (1.3-1.5): (0.4-0.7); the vinyl acetate content of EVA resin No. 1 is 5wt%, and the melt flow rate is 1.2g / 10min (190°C / 2.16kg), DowDuPont, ELVAX TM EVA, model 3120; No. 2 EVA resin has a vinyl acetate content of 8wt%, a melt flow rate of 3g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 265. The vinyl acetate content of EVA resin No. 3 is 25wt%, and the melt flow rate is 19g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, Model 350.
[0025] The present invention can improve the elongation at break of the inner tube by adding EVA resin to the masterbatch. EVA resin has certain flexibility due to the presence of vinyl acetate monomer. Adding EVA to butyl rubber can improve the flexibility of the composite material, thereby improving the elongation at break. At the same time, EVA has good compatibility with butyl rubber and can be well dispersed in the butyl rubber matrix. This good compatibility helps to distribute the stress inside the material more evenly when subjected to external force, reduce stress concentration, and thus improve the elongation at break. At the same time, the tear strength of the inner tube can be improved.
[0026] Furthermore, the preparation method of the modified filler comprises the following steps: by weight,
[0027] (1) mixing nano silicon dioxide, nano calcium carbonate and nano zinc oxide to obtain a mixed nano filler;
[0028] (2) mixing a mixed filler, anhydrous ethanol and a silane coupling agent KH550 in a weight ratio of 1: (8-10): (0.1-0.2) uniformly, reacting at 40-45° C. for 3-5 hours, filtering, washing and vacuum drying to obtain an aminosilane-modified filler;
[0029] (3) Mix aminosilane modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile in a weight ratio of 30: (80-90): (2.2-2.5): (0.15-0.2), stir and react at 60-65° C. for 4-6 hours, cool to room temperature, stand for 25-30 hours, filter, wash and dry to obtain a modified filler.
[0030] Furthermore, the weight ratio of nano silicon dioxide, nano calcium carbonate and nano zinc oxide is (0.2-0.4):1:(1.5-1.7).
[0031] Furthermore, the particle size of nano-silicon dioxide is 10-25nm, the average particle size is 20nm, and the specific surface area is 150-200m 2 / g; the particle size of nano calcium carbonate is 40-70nm, the average particle size is 50nm, and the specific surface area is 40-60m 2 / g; the particle size of nano zinc oxide is 20-40nm, the average particle size is 34nm, and the specific surface area is 10-20m 2 / g.
[0032] In order to improve the thermal tensile deformation of the inner tube, the present invention attempts to add modified fillers, but the effect is not ideal. The present invention can improve the thermal tensile deformation of the inner tube by modifying the filler. The analysis shows that by mixing nano-silicon dioxide, nano-calcium carbonate and nano-zinc oxide, a composite filler with multiple performance advantages can be obtained. Glycidyl methacrylate can react with the active groups on the surface of the filler to enhance the interaction between the filler and the rubber matrix. The modified filler can improve the dispersibility of the filler and make it more evenly distributed in the butyl rubber system, thereby improving the thermal tensile deformation of the material.
[0033] When a car is used in different seasons and regions, the ambient temperature will vary greatly. Especially in summer or tropical areas, the external ambient temperature is high, and the heat generated during the vehicle driving process will cause the temperature inside the inner tube to rise. High temperature will accelerate the aging process of the rubber material, resulting in performance degradation. Under high temperature conditions, the inner tube needs to maintain its mechanical properties, otherwise, the inner tube may become fragile and fail to work properly. In the system of the present invention, the use of EVA resin with specific parameters and filler with specific parameters can improve the heat-resistant air aging performance of the inner tube. Because the EVA resin and the filler with specific parameters form a stable composite network structure in the butyl rubber matrix. This structure can maintain good stability at high temperatures and is not prone to degradation or aging.
[0034] The invention also provides an environmentally friendly pressure-resistant inner tube prepared by the preparation method.
[0035] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0036] 1. The present invention uses stearic acid as an activator to make desulfurization more thorough, and uses a hydroxyl-containing unsaturated ester to modify the desulfurized rubber material, thereby improving the tensile strength of the environmentally friendly pressure-resistant inner tube.
[0037] 2. The present invention can improve the elongation at break of the inner tube by adding EVA resin to the masterbatch, and can also improve the tear strength of the inner tube.
[0038] 3. The present invention can improve the thermal tensile deformation of the inner tube by modifying the filler with a specific ratio.
[0039] 4. The use of EVA resin with specific parameters and filler with specific parameters in the system of the present invention can improve the heat air aging resistance of the inner tube. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a physical picture of the environmentally friendly pressure-resistant inner tube prepared in Example 1. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The raw materials used in the following examples of the present invention are all commercially available products:
[0043] Neoprene, brand: Covestro (Lanxess), model Neoprene 320-1.
[0044] Paraffin oil, Shandong Mingyue Chemical Co., Ltd., model MY white oil.
[0045] Butyl rubber, brand: Jingboju, grade IIR1953.
[0046] Waste butyl rubber, waste butyl rubber automobile inner tube.
[0047] Rapeseed oil, canola oil, commercially available.
[0048] Example 1
[0049] like Figure 1 As shown, this embodiment provides an environmentally friendly pressure-resistant inner tube, and its preparation method includes the following steps: by weight,
[0050] (1) Weigh the raw materials of the masterbatch, specifically including the following components in parts by weight: 62 parts of butyl rubber, 38 parts of modified waste butyl rubber, 9 parts of EVA resin, 7 parts of chloroprene rubber, 72 parts of carbon black, 7 parts of modified filler, 9 parts of paraffin oil, 5 parts of crosslinking agent hexamethylene diisocyanate, 1.2 parts of stearic acid and 1.7 parts of sulfur;
[0051] (2) Butyl rubber, modified waste butyl rubber, chloroprene rubber, and EVA resin are added to a closed rubber mixer and kneaded at 125° C. for 6 minutes; carbon black and modified filler are continuously added under heat preservation conditions and kneaded for 3 minutes; finally, the remaining components are added and kneaded at 115° C. for 6 minutes to obtain a kneaded rubber, which is molded to obtain a tire tube, which is vulcanized under the following vulcanization conditions: a vulcanization temperature of 175° C., a vulcanization time of 7 minutes, and a pressure of 0.7 MPa to obtain an environmentally friendly pressure-resistant inner tube.
[0052] The preparation method of the modified waste butyl rubber comprises the following steps:
[0053] (1) washing the waste butyl rubber, drying it, and crushing it using a crusher to obtain rubber particles of 60-100 mesh;
[0054] (2) 18 parts by weight of a softener, 2 parts of an activator and 100 parts by weight of rubber particles are mixed, stirred evenly, loaded into a desulfurization device, desulfurized at 210° C. for 12 minutes, cooled, and a desulfurized rubber material is obtained; the softener is a mixture of rapeseed oil, cottonseed oil and rubber seed oil in a weight ratio of 1:1.3:0.7. The activator is stearic acid.
[0055] (3) 100 parts by weight of devulcanized rubber material, 12 parts by weight of hydroxyl-containing unsaturated ester and 2 parts by weight of benzoyl peroxide are mixed, wherein the hydroxyl-containing unsaturated ester includes pentaerythritol diacrylate monostearate, polydipentaerythritol pentaacrylate and pentaerythritol triacrylate in a weight ratio of 1:1.3:0.6, and the mixture is stirred at 125°C for 2.5 hours and cooled to room temperature to obtain modified waste butyl rubber.
[0056] The EVA resin comprises EVA resin No. 1, EVA resin No. 2 and EVA resin No. 3 in a weight ratio of 1:1.4:0.6; the vinyl acetate content of EVA resin No. 1 is 5wt%, and the melt flow rate is 1.2g / 10min (190°C / 2.16kg), DowDuPont, ELVAX TM EVA, model 3120; No. 2 EVA resin has a vinyl acetate content of 8wt%, a melt flow rate of 3g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 265. The vinyl acetate content of EVA resin No. 3 is 25wt%, and the melt flow rate is 19g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, Model 350.
[0057] The preparation method of the modified filler comprises the following steps: by weight,
[0058] (1) Mixing nano-silicon dioxide, nano-calcium carbonate and nano-zinc oxide in a weight ratio of 0.3:1:1.6 to obtain a mixed nano-filler; the nano-silicon dioxide has a particle size of 10-25 nm, an average particle size of 20 nm, and a specific surface area of 150-200 m 2 / g; the particle size of nano calcium carbonate is 40-70nm, the average particle size is 50nm, and the specific surface area is 40-60m 2 / g; the particle size of nano zinc oxide is 20-40nm, the average particle size is 34nm, and the specific surface area is 10-20m 2 / g.
[0059] (2) Mixing a mixed filler, anhydrous ethanol and a silane coupling agent KH550 in a weight ratio of 1:9:0.15, reacting at 42° C. for 4 h, filtering, washing and vacuum drying to obtain an aminosilane-modified filler;
[0060] (3) Aminosilane modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile in a weight ratio of 30:85:2.3:0.17 were mixed, stirred at 62° C. for 5 h, cooled to room temperature, allowed to stand for 28 h, filtered, washed and dried to obtain a modified filler.
[0061] Example 2
[0062] This embodiment provides an environmentally friendly pressure-resistant inner tube, and a preparation method thereof comprises the following steps: by weight:
[0063] (1) Weigh the raw materials of the masterbatch, specifically including the following components in parts by weight: 60 parts of butyl rubber, 40 parts of modified waste butyl rubber, 6 parts of EVA resin, 10 parts of chloroprene rubber, 70 parts of carbon black, 9 parts of modified filler, 6 parts of paraffin oil, 6 parts of crosslinking agent hexamethylene diisocyanate, 1.5 parts of stearic acid and 1.6 parts of sulfur;
[0064] (2) Butyl rubber, modified waste butyl rubber, chloroprene rubber, and EVA resin are added to a closed rubber mixer and kneaded at 130° C. for 5 min; carbon black and modified filler are continuously added under heat preservation conditions and kneaded for 3 min; finally, the remaining components are added and kneaded at 110° C. for 7 min to obtain a kneaded rubber, which is molded to obtain a tire tube, which is vulcanized under the following vulcanization conditions: a vulcanization temperature of 170° C., a vulcanization time of 8 min, and a pressure of 0.6 MPa to obtain an environmentally friendly pressure-resistant inner tube.
[0065] The preparation method of the modified waste butyl rubber comprises the following steps: by weight:
[0066] (1) washing the waste butyl rubber, drying it, and crushing it using a crusher to obtain rubber particles of 60-100 mesh;
[0067] (2) 16 parts by weight of a softener, 3 parts of an activator and 100 parts by weight of rubber particles are mixed, stirred evenly, loaded into a desulfurization device, desulfurized at 220° C. for 10 minutes, cooled, and a desulfurized rubber material is obtained; the softener is a mixture of rapeseed oil, cottonseed oil and rubber seed oil in a weight ratio of 1:1.2:0.8. The activator is stearic acid.
[0068] (3) 100 parts by weight of devulcanized rubber material, 10 parts by weight of hydroxyl-containing unsaturated ester and 3 parts by weight of benzoyl peroxide are mixed, wherein the hydroxyl-containing unsaturated ester includes pentaerythritol diacrylate monostearate, polydipentaerythritol pentaacrylate and pentaerythritol triacrylate in a weight ratio of 1:1.4:0.5, and the mixture is stirred at 120°C for 3 hours and cooled to room temperature to obtain modified waste butyl rubber.
[0069] The EVA resin comprises EVA resin No. 1, EVA resin No. 2 and EVA resin No. 3 in a weight ratio of 1:1.3:0.7; the vinyl acetate content of EVA resin No. 1 is 5wt%, and the melt flow rate is 1.2g / 10min (190°C / 2.16kg), DowDuPont, ELVAX TMEVA, model 3120; No. 2 EVA resin has a vinyl acetate content of 8wt%, a melt flow rate of 3g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 265. The vinyl acetate content of EVA resin No. 3 is 25wt%, and the melt flow rate is 19g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, Model 350.
[0070] The preparation method of the modified filler comprises the following steps: by weight,
[0071] (1) Mixing nano-silicon dioxide, nano-calcium carbonate and nano-zinc oxide in a weight ratio of 0.2:1:1.7 to obtain a mixed nano-filler; the nano-silicon dioxide has a particle size of 10-25 nm, an average particle size of 20 nm, and a specific surface area of 150-200 m 2 / g; the particle size of nano calcium carbonate is 40-70nm, the average particle size is 50nm, and the specific surface area is 40-60m 2 / g; the particle size of nano zinc oxide is 20-40nm, the average particle size is 34nm, and the specific surface area is 10-20m 2 / g.
[0072] (2) mixing a mixed filler, anhydrous ethanol and a silane coupling agent KH550 in a weight ratio of 1:10:0.2, reacting at 45° C. for 3 h, filtering, washing and vacuum drying to obtain an aminosilane-modified filler;
[0073] (3) Aminosilane modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile in a weight ratio of 30:90:2.5:0.2 were mixed, stirred at 65° C. for 6 h, cooled to room temperature, allowed to stand for 30 h, filtered, washed and dried to obtain a modified filler.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is: the raw materials of the masterbatch body are weighed, specifically including the following components in parts by weight: 70 parts of butyl rubber, 30 parts of modified waste butyl rubber, 2 parts of EVA resin, 14 parts of chloroprene rubber, 72 parts of carbon black, 7 parts of modified filler, 9 parts of paraffin oil, 5 parts of cross-linking agent hexamethylene diisocyanate, 1.2 parts of stearic acid and 1.7 parts of sulfur.
[0076] Comparative Example 2
[0077] The difference between this comparative example and Example 1 is that the modified waste butyl rubber is only subjected to vulcanization treatment.
[0078] The preparation method of the modified waste butyl rubber comprises the following steps:
[0079] (1) washing the waste butyl rubber, drying it, and crushing it using a crusher to obtain rubber particles of 60-100 mesh;
[0080] (2) 18 parts by weight of a softener, 2 parts of an activator and 100 parts by weight of rubber particles are mixed, wherein the softener is a mixture of rapeseed oil, cottonseed oil and rubber seed oil in a weight ratio of 1:1.3:0.7, and the activator is stearic acid. After stirring evenly, the mixture is loaded into a desulfurization device, desulfurized at 210° C. for 12 minutes, and cooled to obtain modified waste butyl rubber.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 1 is that the EVA resin comprises EVA resin No. 1, EVA resin No. 2 and EVA resin No. 3 in a weight ratio of 1:1:1; the vinyl acetate content of EVA resin No. 1 is 5wt%, and the melt flow rate is 1.2g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 3120; No. 2 EVA resin has a vinyl acetate content of 8wt%, a melt flow rate of 3g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 265. The vinyl acetate content of EVA resin No. 3 is 25wt%, and the melt flow rate is 19g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, Model 350.
[0083] Comparative Example 4
[0084] The difference between this comparative example and Example 1 is that the vinyl acetate content of EVA resin No. 1 is 9.5wt%, the melt flow rate is 0.8g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 770; No. 2 EVA resin has a vinyl acetate content of 12 wt%, a melt flow rate of 0.35 g / 10 min (190°C / 2.16 kg), DowDuPont, ELVAX TM EVA, model 670. The vinyl acetate content of EVA resin No. 3 is 40wt%, and the melt flow rate is 3g / 10min (190℃ / 2.16kg), DowDuPont, ELVAX TM EVA, model 40L-03.
[0085] Comparative Example 5
[0086] The difference between this comparative example and Example 1 is that nano silicon dioxide, nano calcium carbonate and nano zinc oxide are mixed in a weight ratio of 1:1:1.
[0087] Comparative Example 6
[0088] The difference between this comparative example and Example 1 is that the particle size of nano calcium carbonate is 150-200nm, the average particle size is 165nm, and the specific surface area is 10-20m 2 / g; the particle size of nano zinc oxide is 70-100nm, the average particle size is 85nm, and the specific surface area is 5-10m 2 / g; the particle size of nano-silicon dioxide is 45-60nm, the average particle size is 55nm, and the specific surface area is 100-140m 2 / g.
[0089] Comparative Example 7
[0090] The difference between this comparative example and Example 1 is that the preparation method of the modified filler comprises the following steps: by weight,
[0091] (1) Mixing nano-silicon dioxide, nano-calcium carbonate and nano-zinc oxide in a weight ratio of 0.3:1:1.6 to obtain a mixed nano-filler; the nano-silicon dioxide has a particle size of 10-25 nm, an average particle size of 20 nm, and a specific surface area of 150-200 m 2 / g; the particle size of nano calcium carbonate is 40-70nm, the average particle size is 50nm, and the specific surface area is 40-60m 2 / g; the particle size of nano zinc oxide is 20-40nm, the average particle size is 34nm, and the specific surface area is 10-20m 2 / g.
[0092] (2) Mix the mixed filler, anhydrous ethanol and silane coupling agent KH550 in a weight ratio of 1:9:0.15, react at 42°C for 4 hours, filter, wash and vacuum dry to obtain a modified filler.
[0093] Performance Testing
[0094] The environmentally friendly pressure-resistant inner tubes prepared in Examples 1-2 and Comparative Examples 1-7 were subjected to performance tests.
[0095] The GT-AT-3000 universal tensile testing machine produced by Taiwan High Speed Rail was used to test the tensile stress-strain performance in accordance with GB / T528-2009, the tear strength in accordance with GB / T529-2008, and the hot air aging test in accordance with GB / T3512-2001: 100°C × 72h, and the tensile strength retention rate was calculated as follows: tensile strength after aging / tensile strength before aging × 100%; elongation at break retention rate = elongation at break after aging / elongation at break before aging × 100%. The hot tensile deformation was determined in accordance with GB / T7036.1-2009.
[0096] Table 1 Performance test results
[0097]
[0098] It can be seen from the above performance test results that the environmentally friendly pressure-resistant inner tubes of Examples 1-2 have excellent comprehensive performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of multiple components.
[0099] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the composition of the raw materials of the masterbatch body is changed, and it can be seen that the comprehensive effects of the inner tube are reduced to varying degrees, proving that the scheme of compounding specific components has an important influence on the performance of the inner tube. In comparative example 2, the modified waste butyl rubber is only vulcanized, resulting in a decrease in tensile strength. In comparative example 3, the composition ratio of the EVA resin is different, and the elongation at break and the tear strength are reduced. In comparative example 4, the parameters of EVA resin No. 1, EVA resin No. 2 and EVA resin No. 3 are different, and the heat-resistant air aging performance is reduced. In comparative example 5, the ratios of nano-silicon dioxide, nano-calcium carbonate and nano-zinc oxide are different, and the heat-resistant air aging performance is reduced; in comparative example 6, the parameters of the filler are different, and the heat-resistant air aging performance is reduced; in comparative example 7, the modification method of the filler is different, and the heat-resistant air aging performance is reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0100] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an environmentally friendly pressure-resistant inner tube, characterized in that: The preparation method comprises the following steps: by weight, (1) Weighing the raw materials of the masterbatch, specifically including the following components in parts by weight: 60-65 parts of butyl rubber, 35-40 parts of modified waste butyl rubber, 6-11 parts of EVA resin, 5-10 parts of chloroprene rubber, 70-75 parts of carbon black, 4-9 parts of modified filler, 6-12 parts of paraffin oil, 3-6 parts of crosslinking agent, 1-1.5 parts of stearic acid and 1.6-1.8 parts of sulfur; (2) adding butyl rubber, modified waste butyl rubber, chloroprene rubber, and EVA resin into a closed rubber mixer, and kneading at 120-130° C. for 5-7 minutes; continuing to add carbon black and modified filler under heat preservation conditions, and kneading for 2-3 minutes; finally adding the remaining components, and kneading at 110-120° C. for 5-7 minutes to obtain a rubber mixture, molding the rubber mixture to obtain a tire tube, and vulcanizing the tire tube to obtain an environmentally friendly pressure-resistant inner tube; The preparation method of the modified waste butyl rubber comprises the following steps: (1) washing the waste butyl rubber, drying it, and crushing it using a crusher to obtain rubber particles of 60-100 mesh; (2) 16-20 parts by weight of a softener, 1-3 parts of an activator and 100 parts by weight of rubber particles are mixed, stirred evenly, loaded into a desulfurization device, desulfurized at 200-220° C. for 10-15 min, cooled, and a desulfurized rubber material is obtained; (3) 100 parts by weight of devulcanized rubber material, 10-13 parts by weight of hydroxyl-containing unsaturated ester and 1-3 parts by weight of benzoyl peroxide are mixed, stirred at 120-130° C. for 2-3 hours, and cooled to room temperature to obtain modified waste butyl rubber.
2. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 1, characterized in that: The softener is a mixture of rapeseed oil, cottonseed oil and rubber seed oil in a weight ratio of 1: (1.2-1.4): (0.5-0.8).
3. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 1, characterized in that: The activator is stearic acid.
4. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 1, characterized in that: The hydroxyl-containing unsaturated ester includes pentaerythritol diacrylate monostearate, polydipentaerythritol pentaacrylate and pentaerythritol triacrylate in a weight ratio of 1:(1.2-1.4):(0.5-0.7).
5. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 4, characterized in that: The crosslinking agent is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, and methylene diphenyl diisocyanate.
6. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 1, characterized in that: The EVA resin comprises EVA resin No. 1, EVA resin No. 2 and EVA resin No. 3 in a weight ratio of 1: (1.3-1.5): (0.4-0.7); the vinyl acetate content of EVA resin No. 1 is 5wt%, and the melt flow rate is 1.2g / 10min under the condition of 190℃ / 2.16kg; the vinyl acetate content of EVA resin No. 2 is 8wt%, and the melt flow rate is 3g / 10min under the condition of 190℃ / 2.16kg; the vinyl acetate content of EVA resin No. 3 is 25wt%, and the melt flow rate is 19g / 10min under the condition of 190℃ / 2.16kg.
7. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: by weight, (1) mixing nano silicon dioxide, nano calcium carbonate and nano zinc oxide to obtain a mixed nano filler; (2) mixing a mixed filler, anhydrous ethanol and a silane coupling agent KH550 in a weight ratio of 1: (8-10): (0.1-0.2) uniformly, reacting at 40-45° C. for 3-5 hours, filtering, washing and vacuum drying to obtain an aminosilane-modified filler; (3) Mix aminosilane modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile in a weight ratio of 30: (80-90): (2.2-2.5): (0.15-0.2), stir and react at 60-65° C. for 4-6 hours, cool to room temperature, stand for 25-30 hours, filter, wash and dry to obtain a modified filler.
8. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 7, characterized in that: The weight ratio of nano silicon dioxide, nano calcium carbonate and nano zinc oxide is (0.2-0.4):1:(1.5-1.7).
9. The method for preparing an environmentally friendly pressure-resistant inner tube according to claim 8, characterized in that: The particle size of nano-silicon dioxide is 10-25nm, the average particle size is 20nm, and the specific surface area is 150-200m 2 / g; the particle size of nano calcium carbonate is 40-70nm, the average particle size is 50nm, and the specific surface area is 40-60m 2 / g; the particle size of nano zinc oxide is 20-40nm, the average particle size is 34nm, and the specific surface area is 10-20m 2 / g.
10. An environmentally friendly pressure-resistant inner tube made according to the preparation method of claims 1-9.
Citation Information
Patent Citations
Grafting modification process of regenerating waste butyl rubber
CN101020734A
Mixing butyl rubber for anti-aging truck inner tube
CN105001530A
Application of modified calcium carbonate in cable rubber sheath
CN107540905A
Construction composite material with high strength and high wear resistance and preparation method thereof
CN108359150A
High-performance heavy calcium carbonate and activation modification preparation method thereof
CN116948258A